2022
DOI: 10.1371/journal.pone.0274681
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to tourism demand at major Japanese hot springs

Abstract: Hot springs are a major tourism resource in nature-based tourism, and the hot springs market is one of the biggest sectors in wellness tourism markets. In the present study, we examine factors contributing to tourism demand for major hot spring resorts in Japan using ordinary least squares regression models and generalized linear mixed models, and compare the estimation results. The results show that significant factors in most of our models are quality of accommodations and the degree of dependence on inbound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Two GLMM models were considered. The baseline GLMM model involved a log link function (see also [ 21 ]) and was given by: In Eq ( 1 ) the variable receipts pt describes the receipts of province p at time t , where t measures time in calendar quarters, β (0) denotes the fixed intercept, indices k and l count the m independent variables of the final pool, x (k) pt with k = 1,…, m denote the independent variables of that pool measured for province p at time t . Moreover, β ( k ) and β ( kl ) denote the regression coefficients of the main and interaction effects of factor k and factors kl , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two GLMM models were considered. The baseline GLMM model involved a log link function (see also [ 21 ]) and was given by: In Eq ( 1 ) the variable receipts pt describes the receipts of province p at time t , where t measures time in calendar quarters, β (0) denotes the fixed intercept, indices k and l count the m independent variables of the final pool, x (k) pt with k = 1,…, m denote the independent variables of that pool measured for province p at time t . Moreover, β ( k ) and β ( kl ) denote the regression coefficients of the main and interaction effects of factor k and factors kl , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, Raharti et al [ 25 ] showed for data from Yogyakarta city, Indonesia, for the period of 2005 to 2018 that the number of tourists had a significant effect on the revenues coming from the tourism sector. More recently, Medai et al [ 21 ] showed that roughly speaking the number of visitors had a positive effect on the tourism revenues obtain from hot spring areas of Japan when focusing on the year 2018 and considering the major ten Japanese hot springs. When studying factors determining the number of foreign visitors, it has been suggested to take a measure for the cost of living for tourists at their destinations into account.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…China is rich in hot spring resources, with an estimate of over 2000 hot spring spots in rural areas [5]. The hot spring industry provides about two million jobs each year, creating an output value of about USD 200 billion [6]. The development of hot spring resources plays an important and positive role in increasing the employment of villagers, improving rural financial income, promoting the sustainable development of rural industries, and achieving common prosperity [7,8].…”
Section: Introductionmentioning
confidence: 99%